1983
DOI: 10.1111/j.1476-5381.1983.tb10727.x
|View full text |Cite
|
Sign up to set email alerts
|

The potentiation of taurocholate‐induced rat gastric erosions following parenteral administration of cyclo‐oxygenase inhibitors

Abstract: Subcutaneous administration of anti‐inflammatory doses of aspirin, indomethacin, naproxen and flurbiprofen inhibited prostacyclin formation ex vivo in the luminally‐perfused gastric mucosa of anaesthetized rats. These doses of anti‐inflammatory compounds potentiated the formation of gastric mucosal erosions following 3 h luminal perfusion of the topical irritant, acidified sodium taurocholate (2 mm in 100 mm HCl). The increase in luminal acid‐loss during gastric perfusion of acidified taurocholate was not sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
33
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 18 publications
3
33
0
Order By: Relevance
“…Injury to the gastric mucosa is associated with an increase in GMBF (20). Whittle (21) reported that application of acidified TC to the stomach induced a hyperemic response, and this GMBF response was inhibited by concurrent admin istration of indomethacin, in agreement with the present findings. Ablation of capsaicin-sensitive sensory neurons also inhibited the hyperemic response induced by TC.…”
Section: Discussionsupporting
confidence: 82%
“…Injury to the gastric mucosa is associated with an increase in GMBF (20). Whittle (21) reported that application of acidified TC to the stomach induced a hyperemic response, and this GMBF response was inhibited by concurrent admin istration of indomethacin, in agreement with the present findings. Ablation of capsaicin-sensitive sensory neurons also inhibited the hyperemic response induced by TC.…”
Section: Discussionsupporting
confidence: 82%
“…COX-1 is constitutively expressed in normal gastric mucosa and considered to generate PGs involved in the maintenance of essential physiological functions (Whittle, 1983;Simmons et al, 1991;Futaki et al, 1993). Mucosal PGE 2 content in the normal stomach was significantly decreased by SC-560 but not rofecoxib.…”
Section: Cox Isozymes and Gastric Barrier Disruption 717mentioning
confidence: 99%
“…These agents damage the surface epithelium of the gastric mucosa, resulting in acid back-diffusion, yet they rarely cause macroscopically visible damage and actually protect the stomach against necrotizing agents (Holzer et al, 1991;Takeuchi et al, 1993). Such hyperemic responses subside in the presence of NSAIDs, suggesting a role for endogenous PGs in this phenomenon (Whittle, 1983;Nobuhara and Takeuchi, 1984;Takeuchi et al, 1986Takeuchi et al, , 1987. We previously reported, using a selective COX-2 inhibitor, that endogenous PGs produced by COX-1 play an important role in maintaining the gastric hyperemic response and mucosal integrity after barrier disruption by taurocholate (TC) Na (Hirata et al, 1997), yet the relative contribution of the COX-1 and COX-2 isozymes to the maintenance of other functional responses such as acid secretion in the stomach after barrier disruption is not entirely clear.…”
mentioning
confidence: 99%
See 2 more Smart Citations